New taxonomic features of fossil clam shrimp Aquilonoglypta (Spinicaudata) and its implication for origin of triglyptids - Li, Gang (Paleontological Research, 2022)
The Triassic clam shrimp genus Aquilonoglypta Novojilov, 1958 was first erected based on a specimen collected from the Lower Triassic along the Laptev Sea coast of Russia. Its original diagnostic ornament was described as fish scale pits. Then, the genus was recovered in the Lower and Middle Triassic in the Ordos Basin in northwestern China. Because the Chinese specimens have punctate ornamentation, they were interpreted as the ancestor of the Jurassic triglyptids. In this study the diagnosis of Aquilonoglypta is revised following a re-examination of the Russian type specimens under a scanning electron microscope (SEM). In Aquilonoglypta growth bands near the umbo are ornamented with polygonal fine reticulation, which transitions to puncta on growth bands in the middle part of the carapace. The ornamentation on growth bands in the ventral part of the carapace clearly shows the transition from the puncta to a size-increasing fine reticulation pattern. This research result shows that Aquilonoglypta could not be the close link with triglyptids because of lacking of the fine reticulation on growth bands in the dorsal part of the carapace in the latter. On the contrary Triglypta Wang, 1984 could be more closely related to Punctatestheria Zhang et al., 2017.